PELAKSANAAN PEMBELAJARAN ENSAMBEL MUSIK DI MTS LUBUK KILANGAN KOTA PADANG - Restu Putra Rio Ilham; Syeilendra Syeilendra; Ardipal Ardipal (FBS Universitas Negeri Padang, 2018)
Abstract This research aims to describe the implementation of learning ensamble music at 7th grade in MTs Lubuk Kilangan, Padang. The type of research was qualitative research with the descriptive analysis approach which was carried out in MTs Lubuk Kilangan. The object of the research was the implementation of learning ensamble music. The research instrument was the researcher itself and assisted by the supporting instruments such as stationery and photo cameras. The technique of data collection was done by observation, interview, and documentation. The results of this study showed that in the process of planning of learning ensamble music has not been run in accordance with the lesson plan. Since there are several indicators of learning that are not reached, in the implementation of learning, the students and teachers became obstructed due to the lack of facilities and infrastructure of learning ensamble music, such as musical instruments, whiteboards, books and modules/students’ worksheet as well as classroom that are not adequate yet. It caused the result of students’ assessment was not perfect and it could be seen from the results of students who did not achieve the minimum passing standards. From the result of the study, it was only half the students who passed it. Then, in the implementation of this learning activity, students have not been able to play a musical instrument with the right technique. Keywords: Ensamble music, Learning implementation.